Prognosis, treatment decision-making and value: A qualitative exploration of the emerging role of breast cancer prognostic assays. - Gillian Parker; Stuart Hogarth; Jennifer Fishman; Fiona A Miller (PLoS ONE)
Background Breast cancer prognostic assays are emerging as tools used by physicians in the cancer treatment decision-making process. This technology is new, and we must interrogate the integration of these assays into clinical practice and their effect on prognosis and treatment for both providers and patients. The objective of this study was to explore perspectives on the use and integration of breast cancer prognostic assays in clinical care. Methods 15 international researcher-physician/scientist key opinion leaders who had conducted studies on breast cancer prognostic assays were interviewed. Participants had conducted studies using five different assays. The interview guide was developed through a literature review and leveraged extensive data collected on key clinical utility outcomes for the assays. All interviews were conducted virtually, recorded, and transcribed verbatim. Data were analysed using thematic analysis. Results Three novel themes emerged from participant's perspectives on the use and value of these assays. The emerging role of prognostic assays to identify overtreatment and unnecessary care was highlighted by the majority of participants. The primary value of these tools is to identify patients who will not benefit from adjuvant chemotherapy. Participants reported that current standard practice is to overtreat and portrayed the binary or definitive results of these assays as an important tool to reduce overtreatment. Participants also provided insights into deliberate efforts to integrate the assays into clinical practice and how improved quality of life and reduction in overtreatment was positioned to justify high cost of the assay. Finally, participants reported how the perspectives and uses of these assays vary significantly in different countries and cultures. This jurisdictional variation in cancer prognosis and treatment was observed as producing uneven and sometimes problematic interpretations of value for the assays. Conclusions The results of this study provide insights into the integration of prognostic assays into healthcare services. The assays are seeking to extend the boundaries of their clinical utility through identifying overtreatment and low value care. Efforts to integrate these assays and justify their high prices are unpacked and reveal complex and contradictory factors. Finally, these results illuminate that the varied approaches to cancer treatment, and varied use of chemotherapy create disparate perceptions of value for the assays.